Consensus Bundle on Prevention of Surgical Site Infections After Major Gynecologic Surgery. (January 2017) - Pellegrini, Joseph E.; Toledo, Paloma; Soper, David E.; Bradford, William C.; Cruz, Deborah A.; Levy, Barbara S.; Lemieux, Lauren A.
Abstract : Surgical site infections are the most common complication of surgery in the United States. Of surgeries in women of reproductive age, hysterectomy is one of the most frequently performed, second only to cesarean birth. Therefore, prevention of surgical site infections in women undergoing gynecologic surgery is an ideal topic for a patient safety bundle. The primary purpose of this safety bundle is to provide recommendations that can be implemented into any surgical environment in an effort to reduce the incidence of surgical site infection. This bundle was developed by a multidisciplinary team convened by the Council on Patient Safety in Women's Health Care. The bundle is organized into four domains: Readiness, Recognition and Prevention, Response, and Reporting and Systems Learning. In addition to recommendations for practice, each of the domains stresses communication and teamwork between all members of the surgical team. Although the bundle components are designed to be adaptable to work in a variety of clinical settings, standardization within institutions is encouraged.